Calonarang Mythology - Putra, I Putu Deva Maha; Jodog, I Made; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
Calonarang mythology depicts the story of Queen Nata Ing Girah (ruler in the village of Girah) which is considered scary because it has magical powers and supernatural. Various mythical stories and magical rituals always color the trail Airlangga in Kahuripan, East Java during the 11th century Javanese Hindu period. Research This aims to create and analyze Calonarang's mythological themes in the work art painting. Therefore, the author raised this story into the form of a work of art painting in this Final Project in partnership with Sanggar Wasundari Kamasan Klungkung Bali. Calonarang Mythology research problems in creation. This is the concept of painting that depicts the Calonarang Mythology, what is the process of creating a work of painting depicting mythology Calonarang, and how Calonarang Mythology paintings look like. Method The research used in this writing is text analysis and study literature. The results of this research are works of art with a mythology theme Calonarang with an explanation of the concept, origins of Calonarang mythology, characteristics main characters, and important events in the story are realized in paintings.